Line Balancing and Performance Improvements: A Case Study of a Television Assembly Plant - S, Munisamy,; S.C, Kok, (Malaysian Journal of Science, 2007)
Ever-increasing customer demand and its diversification necessitates organizations to respond by continuously increasing their production throughput and making changes in their production mix. An important strategy to increase productivity is to improve the efficiency of the production or assembly lines, so that production throughput can be increased close to the production capacity of the system. Line balancing can improve the efficiency of an assembly line. This paper focuses on the assembly line of a local television assembly plant. The objective of this study is to improve the efficiency of the television assembly line by assigning tasks to workstations to balance work across stations such as to minimise the number of works stations along the television assembly line, given the production rate or cycle time. We use a modified incremental utilisation heuristic to redesign the local television assembly plant and show that significant improvements in resource utilisation and reduction in operational costs can be achieved.